Education in Hong Kong, Pre-1841 to 1941 : Fact and Opinion - Sweeting, Anthony (Book collections on Project MUSE., 1990)
Fact and opinion serve as the Yin and Yang of Education in Hong Kong, at least as far as its historical development is concerned. Like the ancient Chinese symbols, educational fact and opinion have persistently interacted to complement each other. This interaction produces at any given time the characteristic, often contentious, and invariably concerned mood adopted by participants and observers towards educational matters in Hong Kong.